2008
DOI: 10.1002/ar.20694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gonadal Hormones on the Cross‐Sectional Area of Pubococcygeus Muscle Fibers in Male Rat

Abstract: Effects of gonadal hormones on dimorphic striated muscles such as the bulbocavernosus/levator ani complex related to male penile erection have been widely studied. However, the action of these hormones on pelvic nondimorphic muscles is not known. In the present study, the sensitivity of the male rat pubococcygeus muscle (Pcm) to gonadal hormones was studied measuring the cross-sectional area (CSA) of its fibers. For this, two experiments were done: in the first, the effect of castration, and in the second the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…In male rats, this muscle is not part of the levator ani complex (Yuan et al, 2003); however, its participation in micturition and ejaculation is highlighted through behavioral studies (Manzo et al, 2000) and by electrical stimulation of its nerve (Manzo et al, 1997). Furthermore, by analyzing the cross-sectional area of its fibers, we have shown that this muscle is sensitive to gonadal hormones (Alvarado et al, 2008), but we still do not know whether this effect is due to a direct action of these hormones on its fibers and/or through the neuromuscular complex, in which hormonal changes affect soma size, synaptic efficiency, and neuromuscular junction size of muscles such as the bulbocavernosus and levator ani (Breedlove and Arnold, 1981;Balice-Gordon et al, 1990;Tanaka and Arnold, 1993).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…In male rats, this muscle is not part of the levator ani complex (Yuan et al, 2003); however, its participation in micturition and ejaculation is highlighted through behavioral studies (Manzo et al, 2000) and by electrical stimulation of its nerve (Manzo et al, 1997). Furthermore, by analyzing the cross-sectional area of its fibers, we have shown that this muscle is sensitive to gonadal hormones (Alvarado et al, 2008), but we still do not know whether this effect is due to a direct action of these hormones on its fibers and/or through the neuromuscular complex, in which hormonal changes affect soma size, synaptic efficiency, and neuromuscular junction size of muscles such as the bulbocavernosus and levator ani (Breedlove and Arnold, 1981;Balice-Gordon et al, 1990;Tanaka and Arnold, 1993).…”
mentioning
confidence: 74%
“…Muscles were then immersed in Helly's fixer for 24 hr, washed with distilled water for 2 hr, and dehydrated in alcohols. Using a similar procedure previously described (Alvarado et al, 2008), 20 transverse serial sections (7 lm each) were obtained from a piece of muscle (4 mm in length) close to the origin, and stained with hematoxylin and eosin.…”
Section: Pcm Extraction and Histological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The discharge stopped when the tail was placed in the midline. Since muscle spindles have been described in the pubococcygeus muscle (Alvarado et al 2008), the activity related to tail contralateral movement may be a reflex response with muscle spindles as afferents. In a prone position, the coccygeus muscle and most of the pubococcygeus recording sites did demonstrate activity during micturition.…”
Section: Resultsmentioning
confidence: 99%
“…Their morphometric characteristics are modulated by gonadal www.intechopen.com steroid hormones, as indicated by soma size and dendrite length and arborization reduction after ovariectomy and recovery after steroid treatment (Cuevas et al 2006). In males it has been shown that the muscle fibers are also sensitive to gonadal steroids since castration reduces the cross-sectional area of the pubococcygeus muscle (Alvarado et al 2008). Afferents involved in induction of reflex activity of pelvic floor muscles travel through the pudendal and pelvic nerves (Pacheco et al 1989).…”
Section: Innervation Of Pelvic Floor Musclesmentioning
confidence: 99%